Integrating Cryptographic Security Features in Information System Barcodes for Self-Service Systems - Sucipto; Aidina Ristyawan; Dwi Harini; Wahid Ibnu Zaman; Muhammad Najibulloh Muzaki; Mohamed Naeem Antharathara Abdulnazar (Science and Technology Research Centre Universitas PGRI Semarang, 2024)
Integrating services in an information system is necessary to provide services that can optimize an information system. One of the systems in PKKMB activities that will be combined with information security features is the attendance system. This research uses the Liner Sequential Model (LSM) method to integrate the QR Code attendance system with security features. This research aims to integrate QR Codes by optimizing increased security by combining the Advanced Encryption Standard (AES) algorithm with base64 with a dynamic data model to complicate the QR Code manipulation process. Contribution This study makes optimization of the AES encryption model to improve data security on QR Code. Algorithm testing results include using a Character Error Rate (CER) of 0%, Avalanche Effect (AE) testing with a value of 53.05%, and response time (RT) testing of 10.26ms